Question
upstudy study bank question image url

नुहोस् (If \( 2 t=5-\sqrt{21} \) then, prove that) : \( t^{3}+\frac{1}{t^{3}}= \) होस् (If \( t=\sqrt{3+\sqrt{5}} \) then, prove that) : \( t^{2}+\frac{4}{t^{2}}=6 \)

Ask by Craig Ray. in Nepal
Nov 11,2024

Upstudy AI Solution

Tutor-Verified Answer

Answer

1. For \( 2t = 5 - \sqrt{21} \), \( t^3 + \frac{1}{t^3} = 110 \). 2. For \( t = \sqrt{3 + \sqrt{5}} \), \( t^2 + \frac{4}{t^2} = 6 \).

Solution

Let's solve the two problems one by one. ### Problem 1: Prove that if \( 2t = 5 - \sqrt{21} \), then \( t^3 + \frac{1}{t^3} = ? \) 1. First, we can express \( t \) in terms of \( \sqrt{21} \): \[ t = \frac{5 - \sqrt{21}}{2} \] 2. Next, we need to find \( t^3 + \frac{1}{t^3} \). We can use the identity: \[ t^3 + \frac{1}{t^3} = \left(t + \frac{1}{t}\right)^3 - 3\left(t + \frac{1}{t}\right) \] 3. To use this identity, we first need to find \( t + \frac{1}{t} \): \[ \frac{1}{t} = \frac{2}{5 - \sqrt{21}} \] To rationalize the denominator: \[ \frac{1}{t} = \frac{2(5 + \sqrt{21})}{(5 - \sqrt{21})(5 + \sqrt{21})} = \frac{2(5 + \sqrt{21})}{25 - 21} = \frac{2(5 + \sqrt{21})}{4} = \frac{5 + \sqrt{21}}{2} \] 4. Now, we can find \( t + \frac{1}{t} \): \[ t + \frac{1}{t} = \frac{5 - \sqrt{21}}{2} + \frac{5 + \sqrt{21}}{2} = \frac{(5 - \sqrt{21}) + (5 + \sqrt{21})}{2} = \frac{10}{2} = 5 \] 5. Now we can substitute \( t + \frac{1}{t} \) into the identity: \[ t^3 + \frac{1}{t^3} = 5^3 - 3 \cdot 5 = 125 - 15 = 110 \] Thus, we have: \[ t^3 + \frac{1}{t^3} = 110 \] ### Problem 2: Prove that if \( t = \sqrt{3 + \sqrt{5}} \), then \( t^2 + \frac{4}{t^2} = 6 \) 1. First, we calculate \( t^2 \): \[ t^2 = 3 + \sqrt{5} \] 2. Next, we need to find \( \frac{4}{t^2} \): \[ \frac{4}{t^2} = \frac{4}{3 + \sqrt{5}} \] To rationalize the denominator: \[ \frac{4}{t^2} = \frac{4(3 - \sqrt{5})}{(3 + \sqrt{5})(3 - \sqrt{5})} = \frac{4(3 - \sqrt{5})}{9 - 5} = \frac{4(3 - \sqrt{5})}{4} = 3 - \sqrt{5} \] 3. Now we can find \( t^2 + \frac{4}{t^2} \): \[ t^2 + \frac{4}{t^2} = (3 + \sqrt{5}) + (3 - \sqrt{5}) = 3 + \sqrt{5} + 3 - \sqrt{5} = 6 \] Thus, we have: \[ t^2 + \frac{4}{t^2} = 6 \] ### Summary of Results 1. For \( 2t = 5 - \sqrt{21} \), we proved that \( t^3 + \frac{1}{t^3} = 110 \). 2. For \( t = \sqrt{3 + \sqrt{5}} \), we proved that \( t^2 + \frac{4}{t^2} = 6 \).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

तपाईंको समीकरणहरूमा कार्य गर्दा, तपाईंले देख्नुहुनेछ कि \( t \) र \( t^2 \) को भावनुसार ठूलो संख्या सिक्नका लागि मूल सिद्धान्तहरूको अध्ययन महत्त्वपूर्ण छ। उदाहरणका लागि, \( t = \sqrt{3 + \sqrt{5}} \) संग जडान गर्दा \( t^2 \) को फलनले नयाँ र रोचक मूल्याङ्कनहरू खुल्न सक्छ। दोस्रो समीकरणको समाधान गर्दा, न केवल प्रभावकारी तरिकाले गणना गर्दै, तर प्रविधिहरू जस्तै बीजगणित, त्रिकोणमिति र रैखिक समीकरणको सहारा लिनु महत्वपूर्ण हुन्छ। यसले समस्या समाधान गर्ने प्रक्रियामा प्रभावकारीता र सटीकता ल्याउँछ।

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy